Histopathology of Venerid Clams Leucoma (=Protothaca) jedoensis (Lischke, 1874) Occurring on the South Coast of Korea - Subramaniam, T.; Kwang-Sik Choi (Korea Institute of Ocean Science & Technology and The Korean Society of Oceanography, 2023)
Commonly occurring on a shallow subtidal coarse sand bottom in the northwest Pacific region, the Jedo Venus clam Leucoma (=Protothaca) jedoensis (Lischke, 1874) is one of the valuable shellfish resources supporting the local fisheries industry on the south coast of Korea. In this study, we surveyed the pathologic condition of L. jedoensis from a shallow subtidal sand flat in Gamakman Bay on the south coast using histology and Ray’s fluid thioglycollate medium (RFTM) assay to diagnose infection by the protozoan pathogen Perkinsus olseni. In September 2022, a total of 200 clams with shell length (SL) ranging from 29 to 50 mm were obtained from Gamakman Bay, and each clam was subjected to histology and RFTM assay. Histology revealed that all clams collected in September were in the resting stage, indicating that L. jedoensis in the study area completed spawning before September. Perkinsus olseni and unidentified trematode in the sporocysts stage were observed in histology with a low prevalence of 1.5% and 1%, respectively. Contrary to the histology, the RFTM assay indicated that 4.5% of the Jedo Venus clams examined in this survey were infected with P. olseni, with an average infection intensity of 1.1 x 104 cells/g gill, highlighting the presence of P. olseni in the area. The histology and RFTM assay suggested that P. olseni may not exert a substantial impact on Jedo Venus clam health, compared to Manila clams, the host of P. olseni occurring in the south coast exhibiting extremely high levels of P. olseni infection intensities and prevalence.
Keywords: Leucoma jedoensis; Perkinsus olseni; Trematodes; Histopathology; Korea